2013
DOI: 10.4267/2042/51217
|View full text |Cite
|
Sign up to set email alerts
|

Praeorbitolina claveli n.sp. (benthic Foraminifera) from the Lower Aptian sensu lato (Bedoulian) of Central Iran

Abstract: Abstract:The new orbitolinid foraminifer, Praeorbitolina claveli n.sp., is described from the Lower Aptian (Bedoulian) of Central Iran. It is characterized by an eccentric embryonic apparatus displaying both a subdivided subembryonic zone and a deuteroconch. The Barremian-Aptian orbitolinid association of this area has a typical northern Tethyan character (e.g., "association à Valserina" of CHERCHI and SCHROEDER, 1973).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…pachymarginalis was initially described from the Bedoulian-Gargasian boundary (Schroeder, 1965). It is frequently mentioned from uppermost Bedoulian (Mancinelli and Chiocchini, 2006) or upper Bedoulian-Gargasian (Schlagintweit et al 2013a(Schlagintweit et al , 2013b) deposits, and was recently reported from the lower Barremian-Bedoulian (Yazdi-Moghadam et al, 2017). The stratigraphic range of the orbitolinids from the Gelian section is consistent with the above-mentioned distributional data (Fig.…”
Section: Figsupporting
confidence: 89%
“…pachymarginalis was initially described from the Bedoulian-Gargasian boundary (Schroeder, 1965). It is frequently mentioned from uppermost Bedoulian (Mancinelli and Chiocchini, 2006) or upper Bedoulian-Gargasian (Schlagintweit et al 2013a(Schlagintweit et al , 2013b) deposits, and was recently reported from the lower Barremian-Bedoulian (Yazdi-Moghadam et al, 2017). The stratigraphic range of the orbitolinids from the Gelian section is consistent with the above-mentioned distributional data (Fig.…”
Section: Figsupporting
confidence: 89%
“…(i.e., Deshayesi-Furcata ammonite zones) (SCHROEDER et al, 2010). In Iran, it was found in Bedoulian strata too (SCHLAGINTWEIT et al, 2013). In Lebanon it was first reported by MOULLADE and SAINT-MARC (1975: Pl.…”
Section: 2) Benthic Foraminifersmentioning
confidence: 87%
“…1): the Anarak section near Anarak and the Herisht sections (T and H) close to Ardakan. First results indicate that the stratigraphy of these carbonates, in Iranian geology often designated as "Orbitolina limestones" (e.g., Stöcklin, 1971), may be highly different (e.g., Schlagintweit et al, 2013). In fact, orbitolinid foraminifera represent frequent constituents in these carbonates, mostly wacketo packstones, where bioerosional processes may affect their tests.…”
Section: Geological Settingmentioning
confidence: 93%